Management Preparation for Computer Automation: Emergent Patterns and Problems - Burack, Elmer H.; Sørensen, Peter (Academy of Management Journal, 1976)
This article analyzes the preparation being done by the management with regard to the implementation of computer automation. The study as well as supplementary information implies that management's computer preparation often seriously lags installation, is narrowly conceived, incomplete or may never even take place. In addressing the issue, the authors suggest giving significantly greater attention to adequate management development policies and strategies in connection with the introduction of new technologies.